Market Analysis to Improve the Performance of Business on Tofu “TAKWA’ Industry in Kediri - Mustaniroh, Siti Asmaul; Wijana, Susinggih; Nastain, Nasrul (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
TAKWA tofu is a kind of tofu which is very popular in Java and Kediri is well known as a center of its industries. Such industries provide thousands of work places, and the annual economic transaction related to the industries is estimated not less than 6.3 billions rupiah. This research was focused to study aspects of marketing, particularly demand forecasting by means of an estimation of total demand, a market stucture using a method knowns as the Structure-Conduct-Performance (SCP), the use of marketing mix to evaluate the competition and marketing strategy.The study was based on the data available from 5 small to medium scales tofu industries in Kediri, from 2003 to 2006. The results showed that the type of the market structure identified was a non-collutive and monopolistic and the competition was based on the ability of producers to vary the types of the products. The demand for the products was still promising and thus the business was feasible. Therefore, based on the average business opportunity, the chance to increase the productivity level as high as 25% up from the existing level is 88.84%. Moreover, based on the four P’s (product, promotion, price and place), in order to increase the sales, it is advised that the producers will be able to improve the quality and packaging of the product, to determine a better range of price, to provide a better promotion and more outlets (retailers). Keywords: Marketing analysis, tofu industry, sales